Ubezpieczenia ograniczonego ryzyka jako nowoczesna forma zarządzania ryzykiem przedsiębiorstwa - Więckowska, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Finite risk insurance and reinsurance there are both methods of Alternative Risk Transfer. Finite risk bases on pooling the risk over time (not over geographic regions as in traditional insurance contracts). Usually only the one entity is insured but for many years - losses will occur during some or none years. The article describes main types of finite risk insurance, which are divided into two main groups: prospective and retrospective insurance with providing some practical examples of using them. Author also compares the expected cost of traditional insurance with finite risk one. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 487-496